"Other Information" in an Audit (Part 2) - FOO S.L., (Institutional Knowledge at Singapore Management University, 2016)
In light of the new reporting requirements, SSA 720 (Revised) articulates a systematic approach on Other Information (OI) work. It comprises five key elements. These are Obtaining, Reading and Considering, Responding, Reporting and Documentation of OI (Figure 1). Invariably, these enhancements provide useful guidance to the auditors. With additional prescribed work efforts, it also calls for a greater integration of OI work scope with the overall audit planning.